A serpentine path: the impact of legal decisions on aboriginal rights and title on the conduct of treaty negotiations in British Columbia - Richmond, Patrick André (2007)
Legal decisions on Aboriginal rights and title and treaty negotiations with First Nations in British Columbia (BC) are inextricably linked. While much has been written on the impacts of a small number of such legal decisions, there has been very little research that critically examines how legal decisions on Aboriginal rights and title, in general, influence the way the parties to the BC treaty process conduct treaty negotiations. In-depth interviews with ten First Nations, provincial, and federal chief negotiators/advisers, together with British Columbia Treaty Commission (BCTC) commissioners and senior-level program staff, suggest that legal decisions on Aboriginal rights and title influence the conduct of treaty negotiations in an indirect and serpentine manner. Further to this, the results suggest that legal decisions on Aboriginal rights and title may act to simultaneously facilitate and constrain the conduct of negotiations.